2006
DOI: 10.1111/j.1540-6229.2006.00173.x
|View full text |Cite
|
Sign up to set email alerts
|

Big House, Little House: Relative Size and Value

Abstract: How do markets value relative house size in a neighborhood? The literature offers differing rationales: atypical houses sell for less, capitalization of property taxes penalizes larger and benefits smaller houses in mixed neighborhoods and conspicuous consumption reinforces the value of relatively larger houses and reduces the value of relatively smaller houses to consumers. Using a simultaneous price-liquidity model that controls for neighborhood supply and demand conditions, this article finds a dominant tax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
4
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 14 publications
1
41
4
1
Order By: Relevance
“…White (1975) and Brueckner (1981) provide extensions that are perhaps the closest in spirit to Hamilton's original work. 2 A recent study by Turnbull, Dombrow, and Sirmans (2006) is a possible exception, although the authors do not directly test for fiscal impacts. 3 Although this paper's distinction between apartments and single-family residences is not intended to be a direct comparison between "small" and "large" homes, the former distinction implies the latter in most instances.…”
Section: Re-thinking the Property Tax Basementioning
confidence: 92%
“…White (1975) and Brueckner (1981) provide extensions that are perhaps the closest in spirit to Hamilton's original work. 2 A recent study by Turnbull, Dombrow, and Sirmans (2006) is a possible exception, although the authors do not directly test for fiscal impacts. 3 Although this paper's distinction between apartments and single-family residences is not intended to be a direct comparison between "small" and "large" homes, the former distinction implies the latter in most instances.…”
Section: Re-thinking the Property Tax Basementioning
confidence: 92%
“…Earlier studies have confirmed that the geographical location of the observed data are important when modelling house prices and it has been pointed out that the small scale neighbourhood has a substantial effect on the price (Laakso 1997;Karakozova 2005;Turnbull et al 2006;Kiel and Zabel 2007;Leonard and Murdoch 2009). However, a problem is how to capture and formulate location and small scale neighbourhood in an econometric model.…”
mentioning
confidence: 87%
“…If, on the other hand, the shopping externality effect dominates, then increasing surrounding listings will increase selling price, shorten time on the market or both. Neighborhood market condition variables are typically significant in price and selling time equation systems (Turnbull and Dombrow 2006, Turnbull, Dombrow and Sirmans 2006, Turnbull and Zahirovic‐Herbert 2011, 2012, Zahirovic‐Herbert and Turnbull 2008).…”
Section: Data and Variablesmentioning
confidence: 99%